Anxiety and depression of patients with digestive cancer - MATSUSHITA, TOSHIKO; MATSUSHIMA, EISUKE; MARUYAMA, MICHIO (Psychiatry and clinical neurosciences, 2005)
This study sought to characterize the psychological status of digestive cancer patients, and to investigate the relationship between psychological characteristics and clinical factors. Subjects were 85 inpatients scheduled to undergo surgery for digestive cancer and 26 control patients. The Japanese versions of Hospital Anxiety and Depression Scale (HADS) and Zung's Self Rating Depression Scale (SDS) were administered for all subjects before surgery, before discharge, and 6 months after discharge. Changes in HADS and SDS scores across the three examination days for three groups of subjects (advanced‐phase, early phase, and control groups) were compared. The mean scores of anxiety and depression were significantly higher in the advanced‐phase group than in the other two groups. Examination day showed a significant effect on depression; depression increased from before surgery to before discharge, and did not return to the preoperative level at 6 months after discharge, but no significant effect on anxiety. As for the relationship between psychological trends and clinical factors, anxiety in the ‘middle age’ and ‘chemotherapy’ groups was more severe than in the ‘elderly’ and ‘no chemotherapy’ groups. Depression in the ‘medical treatment equipment’, ‘chemotherapy’, and ‘long‐term hospitalization’ groups was more severe than in the ‘no equipment’, ‘no chemotherapy’, and ‘standard‐term hospitalization’ groups. These results suggest that we should pay careful attention to cancer patients undergoing surgery, especially young patients who are constantly at risk of anxiety, and assess their depression taking into account their disease and treatment conditions, especially after the time when their discharge is determined.